CSU industrial hygiene program training needs analysis - Moore, Jillian, author; Brazile, William, advisor; Zarestky, Jill, committee member; Reynolds, Stephen, committee member (Colorado State University. Libraries, 2022)
Graduates of industrial hygiene (IH) programs must be able to meet continuously evolving health and safety needs in a wide variety of occupational settings. Therefore, academic IH graduate programs must regularly evaluate their curricula and solicit input from industry professionals in order to make curricular changes that will better prepare their students for professional roles in industry. The purpose of this study was to identify the training gaps that exist between industry needs, accreditation criteria, and the current curriculum for the CSU Industrial Hygiene graduate program. In Phase 1 of this study, a set of curriculum maps were developed to evaluate training gaps between accreditation criteria, course learning objectives, and course assessment mechanisms for each core course in the IH curriculum. In Phase 2, the research team facilitated two group interviews with the Colorado State University (CSU) IH Advisory Board, collected alumni survey data, and performed a qualitative analysis to identify skills gaps/needs for CSU IH Program graduates. In Phase 1, only one gap was identified between accreditation criteria and IH program course objectives in the nine core departmental courses of the CSU IH graduate curriculum. No gaps were found between IH Program course objectives to course assessment mechanisms. In Phase 2, the research team identified three themes (technical, applied, and soft skills) and selected several skills within each theme that interview participants thought were necessary proficiencies for young IH professionals. The curriculum mapping exercise generally validated the satisfactory accreditation status of the CSU IH Program graduate curriculum. The development of the curriculum mapping tool and evaluation method can aid in providing evidence for the re-accreditation process for the CSU IH Program, as well as other occupational health programs. The skills identified in the qualitative interview and survey data can be incorporated into the curriculum to improve the training of IH students. Additionally, by using qualitative analysis, the researchers uncovered soft skills previously unidentified in IH needs assessments, providing valuable information for all IH graduate programs.
Keywords: curriculum map; needs analysis; STEM program; industrial hygiene; curriculum development; occupational health and safety